Extraction and Characterization of Crude Arabinoxylan from Breadfruit (Artocarpus altilis) - Mokhammad Khoiron Ferdiansyah; Daffa Rossi Ifanka; Sari Suhendriani; Tinta Fera; Arief Rakhman Affandi; Rini Umiyati; Iffah Muflihati (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2026)
Arabinoxylan is a dietary fiber belonging to the non-starch polysaccharide family and is known for its health-promoting properties, such as antioxidant and immunomodulatory effects. However, the extraction efficiency and structural integrity of arabinoxylan are strongly influenced by processing conditions, particularly temperature. Breadfruit (Artocarpus altilis) is a potential local source of arabinoxylan, containing up to 2.49% fiber, yet its extraction characteristics have not been widely investigated. Therefore, this study aimed to determine the effect of different extraction temperatures on the characteristics of crude arabinoxylan extracted from breadfruit using water as the solvent. A completely randomized design with one factor, extraction temperature (40°C, 45°C, and 50°C), was used with a 24-hour extraction period. The crude arabinoxylan obtained was characterized for yield, moisture content, ash content, starch content, and monosaccharide profile using HPLC. The results showed that extraction temperature significantly affected the physicochemical characteristics of crude arabinoxylan. The highest yield (4.1%) was obtained at 50°C, while the lowest starch and ash content occurred at 45°C. HPLC analysis revealed that arabinose was present in all treatments, whereas xylose was not detected; the highest arabinose concentration (1.04%) was found at 40°C. These findings indicate that lower extraction temperatures better preserve arabinose content, while higher temperatures enhance yield, suggesting that extraction temperature plays a crucial role in optimizing both purity and quantity of arabinoxylan from breadfruit.